Quasilocalization of Gravity on a Brane by Resonant Modes - Timothy Hollowood (Physical Review Letters, 2000)
We examine the behaviour of gravity in brane theories with extra dimensions in a non-factorizable geometry. We find that for metrics which are asymptotically flat far from the brane there is a resonant graviton mode at zero energy. The presence of this resonance ensures quasi-localization of gravity, whereby at intermediate scales the gravitational laws on the brane are approximately four dimensional. However, for scales larger than the lifetime of the graviton resonance the five dimensional laws of gravity will be reproduced due to the decay of the four dimensional graviton. We also present a simple classification of the possible types of effective gravity theories on the brane that can appear for general non-factorizable background